A Folkloric Approach to Human Resource Management: Rules and Employees' Epistemic Analyses - Whiteley, Alma (Institute of HR Professional Development (IHPD) Personnel Management Association of Thailand, 2013)
Human resources play a role in business success as Thailand, recovering from the global financial crisis, shows not only recovery but resilience and competitiveness. The empirical study reported here targeted employees from five different organizations to explore the meaning ascribed to rules and the interpretations placed upon them, particularly concerning implementation. The study employed constructivist ontology, interpretive epistemology and qualitative methodology appropriate for investigating the epistemic analyses of employees around rules. Group Support Systems (GSS) technology was used incorporating scenarios and ‘complete this sentence’ data collection methods. Human resource managers are responsible for facilitating formal rules, a central HR activity. The assumption from traditional management history is that employee compliance will happen without question, interpretation or assessment. Contesting this, employees’ engage their interpretive capacities in the informal, folkloric domain. Rules in this domain are rendered relational by employees as they ascribe meaning to them. The data supported the ‘unwritten rules’ concept where rules, where they are considered workable in the employee context will be implemented and conversely. Important data for HR managers are employees’ assessment of whether the rhetoric of rules was perceived as valid or not. Also of importance was employees’ reconstitution of rules when the formal rules were perceived as unworkable, information HR managers need to obtain. Contributions to Thai HR management are the need to develop knowledge and awareness of employees’ epistemic analyses in the folkloric domain and the usefulness of structuration theory in alerting HR managers that employees ascribe meaning to and ‘act upon’ formal rules.